Zirconium chloride lithium solid electrolyte and preparation method thereof

By carrying out the sinking and gasification reactions of zirconium chloride particles in the lithium chloride melt, the problems of low reaction efficiency and poor uniformity in the existing zirconium chloride lithium electrolyte synthesis technology are solved, and efficient and uniform zirconium chloride is achieved. Preparation of lithium solid electrolyte.

CN119340460APending Publication Date: 2025-01-21SANXIANG ADVANCED MATERIALS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411358844.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing technical route for synthesis of lithium zirconium chloride has problems such as low reaction efficiency, insufficient reaction interface, and poor reaction uniformity.

Method used

By adding zirconium chloride particles into the lithium chloride melt, solid-liquid and gas-liquid interface reactions occur, and the sinking and gasification reaction of the zirconium chloride particles in the lithium chloride melt is used to generate a zirconium chloride lithium solid electrolyte.

Benefits of technology

The reaction rate is fast, the reaction is efficient and sufficient, the generated lithium zirconium chloride solid electrolyte is uniform and stable, and the manufacturing cost is relatively low.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of electrolyte preparation, and particularly relates to a lithium zirconium chloride solid electrolyte and a preparation method thereof. The preparation method comprises the following steps: adding zirconium chloride particles into a lithium chloride melt for interface reaction, and after the reaction is finished, cooling to obtain the lithium zirconium chloride solid electrolyte. According to the preparation method, the zirconium chloride particles are added into the lithium chloride melt for solid-liquid and gas-liquid interface reaction, the reaction rate is high, the reaction is sufficient and efficient, the cost is relatively low, and the generated zirconium-lithium chloride solid electrolyte is uniform and stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrolyte preparation, and specifically relates to a lithium zirconium chloride solid electrolyte and a preparation method thereof. Background Art

[0002] All-solid-state batteries have become a promising next-generation energy storage technology due to their high safety and high energy density. The development of solid electrolytes with excellent chemical / electrochemical stability, high room temperature ionic conductivity, good positive / negative electrode compatibility and low manufacturing cost is the key to realizing the practical application of all-solid-state batteries. Halide solid electrolytes have attracted widespread attention in the industry due to their advantages such as high positive electrode stability, excellent electrochemical window, good mechanical ductility, acceptable room temperature lithium ion conductivity and good interface stability. The preparation process of lithium zirconium chloride solid electrolytes is simple and easy to achieve large-scale production. It has become one of the strongest competitors for the commercialization of all-solid-state batteries.

[0003] Lithium zirconium chloride solid electrolyte has excellent performance in reducing interfacial impedance, increasing the positive electrode voltage window, and improving the electrolyte oxidation resistance. Therefore, it has important application value and practical prospects in the construction of high-energy density all-solid-state lithium batteries. The preparation process of lithium zirconium chloride solid electrolyte has been a hot topic in industry research in recent years. At present, the existing technical routes for the synthesis of lithium zirconium chloride electrolytes mainly include high-energy ball milling, gaseous zirconium chloride and liquid lithium chloride interfacial reaction synthesis method, etc. For example, the Chinese invention patent with application number 202010972122.2 discloses a method for the preparation of lithium zirconium chloride, in which zirconium chloride and lithium chloride are ball-milled in a certain mass ratio to obtain lithium zirconium chloride. The above technical routes have problems such as low reaction efficiency, insufficient reaction interface, and reaction uniformity. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a lithium zirconium chloride solid electrolyte with high reaction efficiency and good reaction uniformity and a preparation method thereof.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a lithium zirconium chloride solid electrolyte, comprising the following steps: adding zirconium chloride particles into a lithium chloride melt to produce an interfacial reaction, and after the reaction is completed, cooling to obtain a lithium zirconium chloride solid electrolyte.

[0006] Another technical solution adopted by the present invention is: the lithium zirconium chloride solid electrolyte is prepared by the above-mentioned preparation method.

[0007] The beneficial effects of the present invention are as follows: the preparation method of the lithium zirconium chloride solid electrolyte of the present invention adds zirconium chloride particles into a lithium chloride melt to generate solid-liquid and gas-liquid interface reactions, the reaction rate is fast, the reaction is sufficient and efficient, the cost is relatively low, and the generated lithium zirconium chloride solid electrolyte is uniform and stable. DETAILED DESCRIPTION

[0008] In order to explain the technical content, achieved objectives and effects of the present invention in detail, the following is an explanation in conjunction with the implementation modes.

[0009] A method for preparing a lithium zirconium chloride solid electrolyte comprises the following steps: adding zirconium chloride particles into a lithium chloride melt to generate an interface reaction, and after the reaction is completed, cooling to obtain the lithium zirconium chloride solid electrolyte.

[0010] The zirconium chloride particles are zirconium tetrachloride particles.

[0011] From the above description, it can be seen that the beneficial effects of the present invention are: the density of zirconium chloride is 2.8g / cm 3 , the density of lithium chloride is 2.07g / cm 3 . The preparation method of the present invention adds zirconium chloride particles to a lithium chloride melt to generate an interfacial reaction, the density of zirconium chloride is greater than the density of lithium chloride, the zirconium chloride particles slowly sink in the lithium chloride melt, and as the zirconium chloride particles sink, the melt and the zirconium chloride coating corrode and react, while the surface of the zirconium chloride particles quickly vaporizes and sublimates, the zirconium chloride gas floats in the lithium chloride melt and quickly reacts with the lithium chloride melt to generate a lithium zirconium chloride solid electrolyte material. The preparation method has a fast reaction rate, a highly efficient and sufficient reaction, the generated lithium zirconium chloride solid electrolyte is uniform and stable, and the manufacturing cost is relatively low.

[0012] Traditional solid-solid ball milling takes a long time and consumes a lot of energy. However, the solid-liquid-gas three-phase interface reaction combines the atoms and molecules into electrolyte compounds, which is more conducive to the uniformity of the synthetic materials and the improvement of the electrochemical performance.

[0013] Furthermore, the preparation method of the lithium chloride melt comprises the following steps: placing solid lithium chloride in a closed reactor and evacuating the reactor, then heating the reactor to 650-850° C. and keeping the temperature for at least 20 minutes to obtain the lithium chloride melt.

[0014] From the above description, it can be seen that controlling the temperature range to be higher than the melting point makes the melt have better fluidity and reactivity.

[0015] Compared with the solid-solid high-energy ball milling process, although the solid-liquid-gas three-phase interface reaction needs to be heated to above 650°C, it has high reaction efficiency, short time, easy to implement large-scale manufacturing process equipment, high output efficiency, and comprehensive quality and cost considerations, the process has certain advantages.

[0016] Furthermore, in the method for preparing the lithium chloride melt, the heating rate is 2 to 5°C / min.

[0017] Furthermore, in the method for preparing the lithium chloride melt, the vacuum is evacuated to a vacuum degree of ≤10Pa.

[0018] Furthermore, the purity of the solid lithium chloride is ≥98%.

[0019] Furthermore, the interfacial reaction is carried out in a closed reactor, which is a corrosion-resistant alloy-lined ceramic closed reactor or a high-purity dense graphite closed reactor.

[0020] Furthermore, the purity of the zirconium chloride particles is ≥98%, and the particle size is 5 to 100 mm.

[0021] Preferably, the particle size of the zirconium chloride particles is 20 to 50 mm.

[0022] From the above description, it can be seen that in order to fully consider the optimal reaction efficiency of the sinking process, the zirconium chloride particles are designed to have a particle size of 5 to 100 mm. If the particles are too small, they will float on the surface of the melt and be difficult to sink. If the particles are too large, the reaction contact surface will be reduced and the sinking rate will be too fast.

[0023] Furthermore, the interfacial reaction is carried out in an environment with a vacuum degree of ≤10Pa.

[0024] From the above description, it can be seen that the present invention adopts a vacuum degree of ≤10Pa environment to prepare the lithium chloride melt and perform the interface reaction, which can reduce the influence of the air in the environment on the electrolyte performance.

[0025] Furthermore, the molar ratio of lithium chloride to zirconium chloride is 2 to 4:1.

[0026] It can be seen from the above description that the lithium chloride added in the present invention is excessive, and a moderately excessive lithium source is used to supplement the lithium that is subsequently volatilized.

[0027] Another technical solution adopted by the present invention is: the lithium zirconium chloride solid electrolyte is prepared by the above-mentioned preparation method.

[0028] From the above description, it can be seen that the lithium zirconium chloride solid electrolyte of the present invention is uniform and stable, and the average ionic conductivity is ≥4.41×10 -3 S / cm.

[0029] Embodiment 1 of the present invention is: a method for preparing a lithium zirconium chloride solid electrolyte, the steps are as follows:

[0030] Solid lithium chloride and zirconium chloride particles with a purity of ≥98% are weighed in a drying room at a molar ratio of 2:1. The particle size of the zirconium chloride particles is 50 mm. Solid lithium chloride is added to a corrosion-resistant alloy-lined ceramic closed reactor or a high-purity dense graphite closed reactor, and zirconium chloride particles are added to the auxiliary silo of the closed reactor. The sealing device is locked, and the mechanical pump + Roots pump is turned on to pump the vacuum degree in the closed reactor and the silo to 9Pa; the closed reactor is continuously heated to 670°C at 5°C / min, and the temperature is kept for 90 minutes to prepare lithium chloride melt; then the control connecting valve on the connecting pipe between the closed reactor and the silo is opened, and the zirconium chloride particles in the silo are introduced into the lithium chloride melt in the closed reactor for reaction. After the reaction is completed, the solid zirconium chloride particles are obtained after cooling.

[0031] The solid particles of lithium zirconium chloride were ultrafinely ground in a dry inert atmosphere and filtered through a 325 mesh sieve to obtain solid lithium zirconium chloride electrolyte powder. The solid lithium zirconium chloride electrolyte powder was added into a cylindrical mold (Φ15 mm), and a manual tablet press was used to apply a pressure of 360 MPa. The electrolyte sheet was obtained after cold pressing for 3 minutes and demolding. The average ionic conductivity of the electrolyte sheet was 4.41×10- -3 S / cm, indicating that the electrolyte exhibits excellent electrochemical performance.

[0032] Embodiment 2 of the present invention is: a method for preparing a lithium zirconium chloride solid electrolyte, the steps are as follows:

[0033] Solid lithium chloride and zirconium chloride particles with a purity of ≥98% are weighed in a drying room at a molar ratio of 2:1, and the particle size of the zirconium chloride particles is 50 mm; solid lithium chloride is added into a corrosion-resistant alloy-lined ceramic closed reactor or a high-purity dense graphite closed reactor, and zirconium chloride particles are added into an auxiliary silo of the closed reactor, the sealing device is locked, and the mechanical pump + Roots pump is turned on to pump the closed reactor and the silo to a vacuum degree of 6 Pa; the closed reactor is continuously heated to 720°C at 4°C / min, and the temperature is kept for 40 minutes to prepare a lithium chloride melt; then the control connecting valve on the connecting pipe between the closed reactor and the silo is opened, and the zirconium chloride particles in the silo are introduced into the lithium chloride melt in the closed reactor for reaction, and after the reaction is completed, the reaction is cooled to obtain lithium zirconium chloride solid particles.

[0034] The solid particles of lithium zirconium chloride were ultrafinely ground in a dry inert atmosphere and filtered through a 325 mesh sieve to obtain solid lithium zirconium chloride electrolyte powder. The solid lithium zirconium chloride electrolyte powder was added into a cylindrical mold (Φ15 mm), and a manual tablet press was used to apply a pressure of 360 MPa. The electrolyte sheet was obtained after cold pressing for 3 minutes and demolding. The average ionic conductivity of the electrolyte sheet was 7.20×10--3 S / cm, indicating that the electrolyte exhibits excellent electrochemical performance.

[0035] Embodiment 3 of the present invention is: a method for preparing a lithium zirconium chloride solid electrolyte, the steps are as follows:

[0036] Solid lithium chloride and zirconium chloride particles with a purity of ≥98% are weighed in a drying room at a molar ratio of 2:1, and the particle size of the zirconium chloride particles is 50 mm; solid lithium chloride is added into a corrosion-resistant alloy-lined ceramic closed reactor or a high-purity dense graphite closed reactor, and zirconium chloride particles are added into an auxiliary silo of the closed reactor, the sealing device is locked, and the mechanical pump + Roots pump is turned on to pump until the vacuum degree in the closed reactor and the silo is ≤10Pa; the closed reactor is continuously heated to 770°C at 3°C / min, and the temperature is kept for 30 minutes to prepare a lithium chloride melt; then the control connecting valve on the connecting pipe between the closed reactor and the silo is opened, and the zirconium chloride particles in the silo are introduced into the lithium chloride melt in the closed reactor for reaction, and after the reaction is completed, the reaction is cooled to obtain lithium zirconium chloride solid particles.

[0037] The solid particles of lithium zirconium chloride were ultrafinely ground in a dry inert atmosphere and filtered through a 325 mesh sieve to obtain solid lithium zirconium chloride electrolyte powder. The solid lithium zirconium chloride electrolyte powder was added into a cylindrical mold (Φ15 mm), and a manual tablet press was used to apply a pressure of 360 MPa. The electrolyte sheet was obtained after cold pressing for 3 minutes and then demolding. The solid lithium zirconium chloride electrolyte powder was pressed into an electrolyte sheet. The average ionic conductivity of the electrolyte sheet was 6.08×10- -3 S / cm, indicating that the electrolyte exhibits excellent electrochemical performance.

[0038] Embodiment 4 of the present invention is: a method for preparing a lithium zirconium chloride solid electrolyte, the steps are as follows:

[0039] Solid lithium chloride and zirconium chloride particles with a purity of ≥98% are weighed in a drying room at a molar ratio of 2:1, and the particle size of the zirconium chloride particles is 50 mm; solid lithium chloride is added into a corrosion-resistant alloy-lined ceramic closed reactor or a high-purity dense graphite closed reactor, and zirconium chloride particles are added into an auxiliary silo of the closed reactor, the sealing device is locked, and the mechanical pump + Roots pump is turned on to pump until the vacuum degree in the closed reactor and the silo is ≤10Pa; the closed reactor is continuously heated to 850°C at 2.5°C / min, and the temperature is kept for 20 minutes to prepare a lithium chloride melt; then the control connecting valve on the connecting pipe between the closed reactor and the silo is opened, and the zirconium chloride particles in the silo are introduced into the lithium chloride melt in the closed reactor for reaction, and after the reaction is completed, the reaction is cooled to obtain lithium zirconium chloride solid particles.

[0040] The solid particles of lithium zirconium chloride were ultrafinely ground in a dry inert atmosphere and filtered through a 325 mesh sieve to obtain solid lithium zirconium chloride electrolyte powder. The solid lithium zirconium chloride electrolyte powder was added into a cylindrical mold (Φ15 mm), and a manual tablet press was used to apply a pressure of 360 MPa. The electrolyte sheet was obtained after cold pressing for 3 minutes and demolding. The average ionic conductivity of the electrolyte sheet was 5.73×10- -3 S / cm, indicating that the electrolyte exhibits excellent electrochemical performance.

[0041] Comparative Example 1 of the present invention is: preparing lithium zirconium chloride solid electrolyte by solid-solid ball milling method, the steps are as follows:

[0042] Solid lithium chloride and zirconium chloride particles with a purity of ≥98% and a particle size of 50 mm are taken from a drying room, and are put into a planetary ball mill to grind lithium chloride and zirconium chloride to a fineness of 325 meshes respectively using zirconium oxide balls as grinding media. Lithium chloride and zirconium chloride powders are weighed and added to the zirconium oxide grinding tank at a molar ratio of 2:1, and 5mm zirconium oxide beads are added to the grinding tank at a ball-to-material mass ratio of 60:1. The high-energy ball mill speed is set to 550r / min, and the mechanical ball milling synthesis program is set to forward rotation for 5min, rest for 5min, reverse rotation for 5min, and rest for 5min. The ball milling is cycled according to the above program, and the effective grinding time is 20h to obtain lithium zirconium chloride solid electrolyte powder.

[0043] The solid-state lithium zirconium chloride electrolyte powder was ultrafinely ground in a dry inert atmosphere and filtered with a 325-mesh sieve to obtain the solid-state lithium zirconium chloride electrolyte powder. The solid-state lithium zirconium chloride electrolyte powder was added into a cylindrical mold (Φ15 mm), and a manual tablet press was used to apply a pressure of 360 MPa. The electrolyte sheet was obtained after cold pressing for 3 minutes and demolding. The average ionic conductivity of the electrolyte sheet was 2.57×10-1 at 55°C using an electrochemical workstation PARSTAT 3000A. -3 S / cm, indicating that the electrochemical performance of this electrolyte is lower than that of the present application.

[0044] Compared with the solid-liquid-gas three-phase interface reaction at high temperature, the electrolyte is a solid-solid ball-milled mixture, which is prone to agglomeration, dead corners, inconsistent grinding fineness of different materials under the same conditions, mechanical grinding of electrolyte combination ratios and other process defects that limit material uniformity.

[0045] Embodiment 5 of the present invention is: lithium zirconium chloride solid electrolyte prepared by the preparation method of embodiment 1.

[0046] In summary, the lithium zirconium chloride solid electrolyte and preparation method thereof provided by the present invention adopts zirconium chloride particles and lithium chloride melt to carry out interface reaction. Compared with ball milling mixing and gas-liquid interface reaction, during the reaction of solid zirconium chloride and liquid lithium chloride, the zirconium chloride particles continuously sink in the lithium chloride melt of sufficient depth. During the sinking process, the lithium chloride melt coats and corrodes the surface of the zirconium chloride particles to carry out solid-liquid and gas-liquid reactions. The process cost is relatively low, the reaction rate is fast, the reaction is efficient and sufficient, and the generated lithium zirconium chloride electrolyte has uniform and stable quality and excellent electrochemical performance.

[0047] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the specification of the present invention, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a lithium zirconium chloride solid electrolyte, characterized in that: The method comprises the following steps: adding zirconium chloride particles into lithium chloride melt to generate interface reaction, and after the reaction is finished, cooling to obtain zirconium chloride lithium solid electrolyte.

2. The method for preparing the lithium zirconium chloride solid electrolyte according to claim 1, characterized in that: The preparation method of the lithium chloride melt comprises the following steps: placing solid lithium chloride in a closed reactor and evacuating the reactor, then heating the reactor to 650-850° C. and keeping the temperature for at least 20 minutes to obtain the lithium chloride melt.

3. The method for preparing the lithium zirconium chloride solid electrolyte according to claim 2, characterized in that: In the method for preparing the lithium chloride melt, the heating rate is 2-5°C / min.

4. The method for preparing the lithium zirconium chloride solid electrolyte according to claim 2, characterized in that: In the method for preparing the lithium chloride melt, the lithium chloride melt is evacuated to a vacuum degree of ≤10Pa.

5. The method for preparing the lithium zirconium chloride solid electrolyte according to claim 2, characterized in that: The purity of the solid lithium chloride is ≥98%.

6. The method for preparing the lithium zirconium chloride solid electrolyte according to claim 2, characterized in that: The closed reactor is a corrosion-resistant alloy lined ceramic closed reactor or a high-purity dense graphite closed reactor.

7. The method for preparing the lithium zirconium chloride solid electrolyte according to claim 1, characterized in that: The purity of the zirconium chloride particles is ≥98%, and the particle size is 5-100 mm.

8. The method for preparing the lithium zirconium chloride solid electrolyte according to claim 1, characterized in that: The interfacial reaction is carried out in an environment with a vacuum degree of ≤10Pa.

9. The method for preparing the lithium zirconium chloride solid electrolyte according to claim 1, characterized in that: The molar ratio of lithium chloride to zirconium chloride is 2 to 4:

1.

10. A lithium zirconium chloride solid electrolyte prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method and application of lithium zirconium chloride

    CN112062154A